EVALUASI PROGRAM BANTUAN PANGAN NON TUNAI (BPNT) DI KECAMATAN SIEMPAT NEMPU HILIR KABUPATEN DAIRI - Sihombing, Ferlindo; Pasaribu, Vera A; Degedona, L. Primawati (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2023)
The purpose of this study was to determine changes in the mechanism for distributing Non-Cash Food Assistance in Siempat Nempu Hilir District, Dairi Regency, precisely in Jambur Indonesia Village, Janji Village, Sopobutar Village, Laesering Village. Dunn argues that an evaluation can be interpreted as an estimate that gives numbers and values. Evaluation has to do with gathering information about a value or usefulness of obtaining policies in conveying reliable information about work or general regulations using evaluation indicators namely: Effectiveness, Efficiency, Adequacy, Alignment, Responsiveness. The research method used is descriptive qualitative. Data collection techniques used are interviews and documentation. The data was analyzed using the stages of data reduction, data analysis and drawing conclusions. The informants in this research were key informants (District Head of Siempat Nempu Hilir), main informants (BPNT Recipients). The results of this study indicate that changes in the mechanism for distributing Non-Cash Food Assistance are very well received by the community because people can use the assistance for their own needs so that the purpose of the program can work, namely for the welfare of the poor.